IMMUNOMODULATORY EFFECTS OF VITAMIN D AND ITS STATUS IN PATIENTS WITH AUTOIMMUNE DISEASES - Karolina Osińska; Marcin Schulz; Agnieszka Morawa; Dawid Studziński; Anna Kołcz; Michał Kulczak (International Journal of Innovative Technologies in Social Science, 2026)
The incidence of autoimmune diseases is increasing year by year, especially in Western societies. Many factors, both genetic and environmental, are involved, and vitamin D (vD, 25(OH)D3) deficiency is considered to be one of the key factors. However, the precise etiopathogenesis of autoimmune disorders is still not fully understood, which is also reflected in the limitation of therapeutic possibilities. Recently, there has been a growing interest in the role of vitamin D in alleviating autoimmunological processes, as vD has the ability to stimulate or inhibit virtually every stage of the immune response through its vitamin D receptor (VDR), expressed on immune cells.  Innate and adaptive immune system and endothelial membrane stability. This allows us to define this vitamin as a strong immunomodulator in terms of both innate and acquired immunity. The aim of this paper is to present the pathophysiology of selected autoimmune diseases and to demonstrate the modifying properties of vitamin D on the immune system. Our review also demonstrates the scale of deficiency, both in the general population and among individuals diagnosed with autoimmune disease.